Pengaruh Penggunaan Media Pembelajaran Berbasis Komik Terhadap Hasil Belajar Tematik Siswa Kelas V MIS Juhari Ilmi - Rina Ningsih Pardosi; Regina Fredika Sipayung (LP3M KH Yazid Karimullah Institute, 2024)
This study aims to determine the effect of comic media on the learning outcomes of Class V students of MIS Juhari Ilmi. The research approach used is quantitative. The type of quasi-experimental research with post test type, non-equivalent control group design with the number of students in this study were 40 students The data collection technique used was a test. The results of this study were to determine the effect of using thematic comic media on the learning outcomes of grade V elementary school students.